Emergent mechanical thrombectomy for acute stroke using the Mindframe Capture LP system: initial single-center experience. (13th November 2015) - Cerejo, Russell; John, Seby; Bauer, Andrew; Hussain, Muhammad S; Bain, Mark; Rasmussen, Peter; Hui, Ferdinand; Masaryk, Thomas; Toth, Gabor
Abstract : Background: Mechanical thrombectomy using stentrievers is the standard of care for emergent large vessel occlusion stroke. Data on the use of stentrievers in smaller caliber vessels are sparse. Objective: To present our initial experience with the Mindframe Capture LP device, which was designed for mechanical thrombectomy in small cerebral arteries. Methods: A retrospective chart review was conducted of patients who underwent Mindframe device assisted emergent thrombectomy. Clinical, imaging, procedural and early follow-up data were obtained. Results: Nine patients met inclusion criteria (5 men, median age 62 years). Median National Institute of Health Stroke Scale (NIHSS) score was 18 (IQR 9–22), and 6 patients received intravenous tissue plasminogen activator. Six patients had M2 segment occlusions, and 2 patients had distal M1 segment occlusions of the middle cerebral artery. One had distal basilar artery occlusion. Median vessel diameter at the thrombus was 1.7 mm (IQR 1.5–2.5). In all 9 patients the Mindframe device was used together with manual aspiration, with median groin puncture to recanalization time of 35 min (IQR 27–54), and median procedural time of 67 min (IQR 51–91). Final Thrombolysis in Cerebral Infarction score was 3 and 2b in 4 patients each (89% total), and 2a in 1 patient. No patient had any postprocedural complications or symptomatic intracerebral hemorrhage. Median postprocedure and discharge NIHSS were 4 and 1, respectively. Conclusions: Our data suggest that the Mindframe device is safe and effective for rapid treatment of acute strokes involving small caliber intracranial vessels. Further study in a larger cohort is warranted.